Efficacy of Intravenous Sedation, Paracervical Block and Paracervical Block with Lidocaine Spray on Pain Relief during Uterine Curettage in First Trimester Incomplete Abortion: Randomized clinical trial - Pakapong Kerdtawee; Piyawadee Wuttikonsammakit; Parinya Chamnan (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objectives: To evaluate efficacy of intravenous sedation, paracervical block (PCB) and PCB plus lidocaine spray for pain relief during uterine curettage in first trimester incomplete abortion. Materials and Methods: Randomized trial included 121 participants with incomplete abortion at gestational age less than 14 weeks who underwent uterine curettage. They were randomly assigned into three groups: intravenous sedation (meperidine 50 mg and diazepam 10 mg), PCB (5 ml of 1% lidocaine injected at the 4 and 8 o'clock positions of cervix) and PCB plus 10% lidocaine spray 20 mg at the cervix. Pain score was measured using a numerical rating scale (0-10) before, during uterine curettage being undertaken, immediately and 30 minutes after the procedure. Adverse effects were observed and participants' satisfactions were evaluated. Results: Pain score during the uterine curettage was significantly different across the three treatment groups (median score of 5 in intravenous sedation group, 5 in PCB group, 4 in PCB plus spray group, p = 0.001). Further pairwise comparisons found significantly greater benefits on pain relief during the uterine curettage in PCB plus spray than both PCB and intravenous sedation groups (p = 0.001 and 0.002, respectively). Significant differences in pain scores across the three treatment groups were also observed immediately (p = 0.025), and 30 minutes after the procedure (p = 0.003). Satisfaction of pain relief was lower in the intravenous sedation than the PCB and PCB plus spray groups. The intravenous sedation group reported more nausea and dizziness, while the PCB group reported more symptoms of numbness than the other two groups. Conclusion: Paracervical block plus 10% lidocaine spray had high efficacy in pain relief in incomplete abortion uterine curettage with fewer minor adverse effects of nausea and dizziness.